Predação do pixoxó Sporophila frontalis (Aves: Emberizidae) em sementes de Merostachys neesii (Poaceae: Babusoideae) durante um evento de frutificação em massa na floresta atlântica - Cestari, César [UNESP]; Bernardi, Cláudio João [UNESP] (FapUNIFESP (SciELO), 2011)
The Buffy-fronted Seedeater Sporophila frontalis (Verreaux, 1869) is frequently found foraging on seeds during ephemeral masting events of bamboos in the Atlantic forest. In the present study, we analyzed the predation activity of S. frontalis on seeds of Merostachys neesii Rupr. during a masting event in an Atlantic forest reserve on southeastern Brazil. We conducted point counts in spots with M. neesii and in spots without bamboos along trails to determine the presence of S. frontalis on M. neesii clumps. Additionally, focal observations on bamboo clumps and seed traps were used to verify the predatory impact of S. frontalis on M. neesii seeds. S. frontalis was present in 6 out 18 point counts in M. neesii clumps. The seedeater behaved territorially in bamboo clumps and presented a mean predation rate of 1.10 bamboo seeds/minute. Seed traps had up to 80% of the seeds predated. The large amount of seeds available during bamboo masting events probably contributes to the maintenance of wandering populations of S. frontalis in the Atlantic forest. On the other hand, the predation of seeds by S. frontalis may reduce the reproductive germination and the propagation of the bamboos whose growth may in turn negatively affect the establishment of other forest species.
Predation of the Buffy-fronted seedeater Sporophila frontalis (Aves: Emberizidae) on Merostachys neesii (Poaceae: Babusoideae) seeds during a masting event in the atlantic forest
Keywords: Bamboos; Bird-plant interaction; Emberizidae; Foraging behavior; Predation rate